2012
DOI: 10.1002/ptr.4724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Food–drug Interaction of Guava Leaf Tea

Abstract: Guava leaf tea (GLT) contains guava leaf polyphenol (Gvpp), which regulates the absorption of dietary carbohydrate from the intestines. Borderline diabetics, who are at high risk of development of diabetes, take GLT to suppress a rapid increase of blood sugar level after meals. However, patients with diabetes in whom diabetic drugs or warfarin as a blood thinner are prescribed also take GLT with the expectation of glycemic control. Therefore, we studied whether GLT had potential for inhibition or induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Chen et al [34] reported that guava leaf extract with high flavonoid (8.29 ± 0.22 g/100 g) and polyphenolic acid (16.56 ± 10.39 g/100 g) content inhibited brainderived metastatic prostate cancer. In addition, Kaneko et al [35] indicated that the safety of P. guajava has been reported in food-drug interactions in various systems within animals. However, the mechanisms responsible for apoptosis induction by GLE on HepG2 cells has been still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [34] reported that guava leaf extract with high flavonoid (8.29 ± 0.22 g/100 g) and polyphenolic acid (16.56 ± 10.39 g/100 g) content inhibited brainderived metastatic prostate cancer. In addition, Kaneko et al [35] indicated that the safety of P. guajava has been reported in food-drug interactions in various systems within animals. However, the mechanisms responsible for apoptosis induction by GLE on HepG2 cells has been still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the consumption of guava leaf tea was evaluated, in vivo, in the inhibition of cytochrome P450 (CYP) 3A-mediated drug metabolism by the interaction between guava tea and several drugs [11,142]. Matsuda et al [11] investigated the consequence of the ingestion of guava tea for two weeks in rats, and the effect with an anxiolytic drug.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…This weak influence was due to the absence of interaction between the tea and midazolam in the metabolism studied. In addition, two in vivo studies were made in rats, to evaluate the interaction of guava leaf tea with an anti-coagulant drug (warfarin) [142]. Kaneko et al [141] suggested that because the tea contained compounds that block the affinity between the enzyme and phenolic compounds of the tea, long-term administration showed a low probability of causing drug-metabolizing enzymes.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…This was somewhat surprising as many plants have evolved secondary metabolites in order to be resistant against microbes and insects (40) and often possess compounds that inhibit CYP450 in order to potentiate their defences. Although mostly described on a protein level (41)(42)(43)(44), these changes may also occur on a transcript level (37,(45)(46)(47)(48). Furthermore, other reports have demonstrated changes to genes important for xenobiotic disposition such as ABC transporters and Phase II metabolizing enzymes in response to plant extracts, including but not limited to GSTs and QRs (48)(49)(50) all present on this array but not significantly altered.…”
Section: Discussionmentioning
confidence: 99%